2022
DOI: 10.3390/antiox11020268
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Probiotic Lactobacillus plantarum JBC5 Improves Longevity and Healthy Aging by Modulating Antioxidative, Innate Immunity and Serotonin-Signaling Pathways in Caenorhabditis elegans

Abstract: Since the hypothesis of Dr. Elie Metchnikoff on lactobacilli-mediated healthy aging, several microbes have been reported to extend the lifespan with different features of healthy aging. However, a microbe affecting diverse features of healthy aging is of choice for broader acceptance and marketability as a next-generation probiotic. We employed Caenorhabditis elegans as a model to understand the potential of Lactobacillus plantarum JBC5 (LPJBC5), isolated from fermented food sample on longevity and healthy agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 86 publications
(103 reference statements)
4
64
1
1
Order By: Relevance
“…Several antioxidant enzymes including SOD, GPx, GSH, GSSG and HO-1 are secreted to protect cells against oxidative damage. In accordance with other studies, these enzymes were collectively enhanced and ROS production was reduced by our selected LAB [ 53 , 54 , 55 ]. Nrf2 has long been considered a cytoprotective factor regulating anti-inflammatory and anti-oxidative proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Several antioxidant enzymes including SOD, GPx, GSH, GSSG and HO-1 are secreted to protect cells against oxidative damage. In accordance with other studies, these enzymes were collectively enhanced and ROS production was reduced by our selected LAB [ 53 , 54 , 55 ]. Nrf2 has long been considered a cytoprotective factor regulating anti-inflammatory and anti-oxidative proteins.…”
Section: Discussionsupporting
confidence: 91%
“…L. plantarum GKM3 delayed the process of aging, alleviated age-related cognitive impairment, and reduced oxidative stress in mice models [ 121 ]. Recent findings suggest that L. plantarum JBC5 activated the p38 MAPK pathway and its downstream targets in worms ( Caenorhabditis elegans ) to enhance longevity by improving stress resistance, immunity, and other age-associated pathologies [ 122 ]. Other probiotics, such as B. amyloliquefaciens B-1895 and B. subtilis KATMIRA1933 also induce DNA protective and antioxidant activity [ 123 ].…”
Section: Applications To Human Healthmentioning
confidence: 99%
“…For example, a recent study reported that consumption of probiotic Lactobacillus casei CRL 431 in aged mice not only improved the cellular and functional markers of immunosenescence but also restored the age-related loss in the thymus medulla (Balcells et al 2022 ). Probiotic Lactobacillus plantarum JBC5 enhanced the lifespan of Caenorhabditis elegans through the modulation of multiple markers related to oxidative stress and innate immunity (Kumar et al 2022 ). Application of a probiotic cocktail containing 5 Lactobacillus and 5 Enterococcus strains to old mice prevented the leaky gut by improving the expression of tight junction proteins that ultimately prevented unwarranted aggravation of intestinal immune cells and thus inflammation (Ahmadi et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%